Prevalence, Evolution and Prognostic Factors of PASC in a Cohort of Patients Discharged from a COVID Unit - Mariantonietta Pisaturo; Antonio Russo; Pierantonio Grimaldi; Caterina Monari; Simona Imbriani; Klodian Gjeloshi; Carmen Ricozzi; Roberta Astorri; Caterina Curatolo; Roberta Palladino; Francesco Caruso; Francesca Ambrisi; et al. (Biomedicines)
Background and Aim: PASC is a potentially debilitating clinical condition consisting of different general symptoms experienced by about 10% of patients with previous SARS-CoV-2 infection. Our study analyses a cohort of patients with a history of hospitalization for COVID-19 and aims to evaluate prognostic factors for experiencing PASC and to investigate the characteristics of patients experiencing PASC symptoms. Methods: This is an observational, monocentric retrospective study including all adult patients admitted to our COVID unit from 28 February 2020 to 30 April 2022, discharged alive, and having performed at least one follow-up visit at our post-COVID outpatient clinic after a minimum of three months from discharge. Patients who experienced persistent clinical manifestations or the development of new symptoms three months after the initial SARS-CoV-2 infection, with these symptoms lasting for at least two months with no other explanation, were defined as having PASC. Results: A total of 429 patients were discharged alive from our COVID Unit and 244 patients performed at least one follow-up visit in our outpatient clinic. Of these, 134 patients did not experience PASC, while 110 patients experienced PASC. Long-COVID patients were more frequently female (43.6% vs. 31.3%, p = 0.048), more frequently presented throat pain and headache at hospital admission (respectively 8.9% vs. 2.5%, p = 0.041 and 15.8% vs. 5%, p = 0.007), and were more likely to have a history of type 2 diabetes mellitus (25.5% vs. 13%, p =0.013). At the multivariable analysis, female gender, type 2 diabetes, and headache at admission were factors associated with PASC. All 46 patients who performed at least two different admissions in our outpatient clinic were divided in two groups: the first including the 16 patients who experienced a reduction or a resolution of symptoms related to COVID-19, the second comprising the 30 patients who experienced clinical worsening or persisting symptoms. Smoking habit was more represented among patients with stable or worsening symptoms (42.3% vs. 7.7%, p = 0.042); myalgias at admission were more frequent in the clinical worsening group (27.6% vs. 0%, p= 0.039); and a larger amount of patients who reported neuropsychiatric symptoms and respiratory symptoms were in the stable or worsening PASC symptoms group. Discussion: In conclusion, this study underscores the complexity of PASC, identifying female sex, Type 2 diabetes, and certain acute COVID-19 symptoms as potential predisposing factors for its development. PASC still represents a substantial public health challenge, and ongoing efforts are essential to better understand its underlying mechanisms and improve patient outcomes.